ANALISIS DAMPAK GAME ONLINE ROBLOX TERHADAP KEPEKAAN SOSIAL SISWA KELAS V SDN BEKASI JAYA XIII KOTA BEKASI - Syifa Nurul Aini; Widiansyah, Apriyanti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the relationship between the online game Roblox and the social sensitivity of fifth-grade students at SDN Bekasi Jaya XIII, Bekasi City. Social sensitivity in this study encompasses four indicators: empathy, sympathy, tolerance, and helpfulness. The study employs a qualitative approach using a case study method. Data collection was conducted through observation, interviews, and documentation. The results indicate a relationship between the online game Roblox and the students' social sensitivity; students with low playing frequency and low emotional attachment demonstrated high social sensitivity, whereas those with high playing frequency and high emotional attachment tended to exhibit moderate to low social sensitivity. This study seeks to determine the impact of the online game Roblox on the social sensitivity of fifth-grade students at SDN Bekasi Jaya XIII, Bekasi City.